De la niñez a la plena madurez - María Teresa López Beltrán (Mélanges de la Casa de Velázquez)
The journey towards the age of maturity or marriage was a vital, complex stage for women, since it involved risks and mishaps not only for daughters who lived under the jurisdiction of parents and tutors, but also, and above all, for those other young girls who, for various reasons, lacked the protection they needed from their families, which made it more difficult for them to protect their honour during puberty, as well as to gain access in the future to the marriage market.